2002
DOI: 10.1152/ajpcell.00257.2001
|View full text |Cite
|
Sign up to set email alerts
|

Differences in calmodulin and calmodulin-binding proteins in phasic and tonic smooth muscles

Abstract: To determine whether densities of calmodulin (CaM) and CaM-binding proteins are related to phasic and tonic behavior of smooth muscles, we quantified these proteins in the opossum esophageal body (EB) and lower esophageal sphincter (LES), which represent phasic and tonic smooth muscles, respectively. Gel electrophoresis, immunoprecipitation, Western blot, and hemagglutinin epitope-tagged CaM (HA-CaM) overlay assay with quantitative scanning densitometry and phosphorylation measurements were used. Total protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…The different patterns of contractions have been attributed to regional differences in the gene transcription and synthesis of nitric oxide synthetase in the colonic myenteric plexus (33). On the basis of their functional behavior, visceral smooth muscles have been classified into sphincteric and nonsphincteric smooth muscles that represent tonic and phasic muscles (11,16,31). Phasic muscle shows a very wide range of contractile activity that varies from a fully relaxed basal state to a large-amplitude rapid contraction and rapid relaxation response.…”
Section: Discussionmentioning
confidence: 99%
“…The different patterns of contractions have been attributed to regional differences in the gene transcription and synthesis of nitric oxide synthetase in the colonic myenteric plexus (33). On the basis of their functional behavior, visceral smooth muscles have been classified into sphincteric and nonsphincteric smooth muscles that represent tonic and phasic muscles (11,16,31). Phasic muscle shows a very wide range of contractile activity that varies from a fully relaxed basal state to a large-amplitude rapid contraction and rapid relaxation response.…”
Section: Discussionmentioning
confidence: 99%
“…CaM is a ubiquitous calcium-binding protein that is responsible for many intracellular actions of calcium [21][22][23][24][25][26][27][28][29][30] . Lot of evidences suggest that CaM not only plays an important role in the proliferation of normal cells, but also is related to hepatoma growth [2,31] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the GTP-induced Ca 2 þ sensitization was more potent in the proximal than in the distal colon (Figure 2). It was reported that the amount of contractile proteins, the composition of their isoforms and the extent of their phosphorylation are different between phasic and tonic smooth muscle tissues (Lorenz et al, 2002;Szymanski et al, 2002). Ca 2 þ -induced contractions in the proximal colon were smaller than those in the distal colon.…”
Section: T Takeuchi Et Almentioning
confidence: 95%